More Contributions and Notes to a New Campbell Edition - Kronenberg, M.E. author. aut Link
11 p.
Keywords: Perhaps outsiders consider the fact that bibliographies are seldom complete as a depressing circumstance. To the true bibliographer however it is rather exhilirating that by remaining on his qui vive he will probably not fail to find undescribed editions. 1 So, since in 1956 my Contributions to anew Campbell were published , some 23 or 24 unrecorded Low Country incunabula have again come to my notice. They are offered here as a Supplement to the preceding work. I have tried to arrange them in the following list A according to the numbers on which they ought to be placed. In a few instances this offered difficulties, because their right number was already occupied. Then a nearby number had to be used. Under letter B notes and corrections to Chapter I of my former Contributions have been added; under letter C notes, corrections and additions to Chapter II. A few other corrections are given in D. I feel convinced that further research will bring new finds. It is even known to me that Prof. W. G. Hellinga and L. Hellinga have spotted several, the names of which they kindly showed me, but which have not been inserted here. They are going to publish them elsewhere. Still, if again incomplete, the present additions to my Contributions may be of some use. The Hague, September 1963. 1 Quoted further as Contrib. A. ADDITIONS 88c ALBERTUS MAGNUS(?), Secreta mulierum et virorum. (Antwerp, Math. van der Goes, ab. 1490).4°.